General Assembly of the Church of Scotland. (13th December 2013) - Cranmer, Frank
<x content-type="archive" xml:space="preserve">Abstract</x> As always, the General Assembly deliberated on a wide range of issues. Prior to 12 May 1999 the Assembly were regarded by many Scots as the nearest thing to a Parliament that they possessed; and though devolution has perhaps lessened the Assembly's impact it has not diminished their enthusiasm for tackling difficult social and political questions, ranging from the economics of world poverty and the 'Enough food for everyone … if?' campaign to a major report on Israel–Palestine which had attracted considerable criticism from Scotland's Jewish community in advance of the debate. Probably of most interest to readers of this Journal, however, are the following.